Magnetic Seizure Therapy in Treatment-Resistant Schizophrenia: A Pilot Study - Tang, Victor M.; Blumberger, Daniel M.; McClintock, Shawn M.; Kaster, Tyler S.; Rajji, Tarek K.; Downar, Jonathan; Fitzgerald, Paul B.; Daskalakis, Zafiris J. (Frontiers in Psychiatry, 2018)
Objective: Electroconvulsive therapy (ECT) is effective in treatment resistant schizophrenia (TRS) but use is limited due stigma and concerns around cognitive adverse effects. Magnetic seizure therapy (MST) is a promising new neuromodulation technique that uses transcranial magnetic stimulation to induce therapeutic seizures. Studies of MST in depression have shown clinical improvement with a favorable adverse effect profile. No studies have examined the clinical utility of MST in schizophrenia. Methods: We conducted an open label pilot clinical trial of MST in 8 TRS patients. Up to 24 MST treatments were delivered depending on treatment response. We assessed clinical outcome through the Brief Psychiatric Rating Scale (BPRS) and the Quality of Life Enjoyment and Satisfaction Questionnaire (Q-LES-Q). Cognitive testing included a neuropsychological test battery, the Autobiographical Memory Inventory (AMI), Montreal Cognitive Assessment (MoCA), and reorientation time. Results: Four patients completed the trial as per protocol. For all patients and for trial completers alone, there was a significant clinical and quality-of-life improvement. Three met pre-determined criteria for remission (total score ≤25 on the BPRS) and 1 met criteria for response (i.e., ≥25% BPRS improvement from baseline for 2 consecutive assessments). Pre and post neurocognitive data showed no significant cognitive adverse effects apart from a decrease in AMI scores. Conclusion: In this pilot study, MST demonstrated evidence for feasibility in patients with TRS, with promise for clinical efficacy and negligible cognitive side effects. Further study in larger clinical populations is needed. ClinicalTrials.gov Identifier: NCT01596608